Debt, Incarceration, and Re-entry: a Scoping Review - Harper, Annie (American journal of criminal justice, 2021)
People involved with the criminal justice system in the United States are disproportionately low-income and indebted. The experience of incarceration intensifies financial hardship, including through worsening debt. Little is known about how people who are incarcerated and their families are impacted by debt and how it affects their reentry experience. We conducted a scoping review to identify what is known about the debt burden on those who have been incarcerated and their families and how this impacts their lives. We searched 14 data bases from 1990 to 2019 for all original research addressing financial debt held by those incarcerated in the United States, and screened articles for relevance and extracted data from pertinent studies. These 31 studies selected for inclusion showed that this population is heavily burdened by debt that was accumulated in three general categories: debt directly from criminal justice involvement such as LFOs, preexisting debt that compounded during incarceration, and debts accrued during reentry for everyday survival. Debt was generally shown to have a negative effect on financial well-being, reentry, family structure, and mental health. Debts from LFOs and child support is very common among the justice-involved population and are largely unpayable. Other forms of debt likely to burden this population remain largely understudied. Extensive reform is necessary to lessen the burden of debt on the criminal justice population in order to improve reentry outcomes and quality of life.